KEBIJAKAN PERUMUSAN SISTEM PEMIDANAAN YANG BERORIENTASI PADA KORBAN - Eko Soponyono (Masalah-Masalah Hukum, 2012)
Policy of sentencing system in this study in a functional significance (Material Criminal Law, Formal Criminal Law and Law of Punishment Execution). The main problems of this study are (a) How does the formulation of the victim-oriented  sentencing system policy in the current positive law? (b) How does the formulation of victim-oriented sentencing system policy in the future positive law? Research carried out a normative legal research and approaches used include the approach of legislation, conceptual approaches  and comparative approach. Formulation of policy oriented system on victims in the positive law currently only exist on a small portion statutory provisions in Indonesia, while in most of it is still oriented of criminal act offender. Although in its development, emerging concern for the victim, but has not awakened a policy of criminalization of the integral sentencing system. The conclusion that can be put forward is that there is concern for the victims in the current positive law, though not yet awakened a policy of criminalization of the integral system. In the coming policy so the policy was also concerned with both the victims and the offenders.Key word : Sentencing System Formulation, Victim-oriented Policies